New NASICON type oxyanion high capacity anode, Li2Co 2(MoO4)3, for lithium-ion batteries: Preliminary studies - Michael , M.S. (2008)
We describe in this paper the lithium insertion/extraction behavior of a new NASICON type Li2Co2(MoO4)3 at a low potential and explored the possibility of considering this new oxyanion material as anode for lithium-ion batteries for the first time. Li 2Co2(MoO4)3 was synthesized by a soft-combustion glycine-nitrate low temperature protocol. Test cells were assembled using composite Li2Co2(MoO4) 3 as the negative electrode material and a thin lithium foil as the positive electrode material separated by a microporous polypropylene (Celgard® membrane) soaked in aprotic organic electrolyte (1 M LiPF 6 in EC/DMC). Electrochemical discharge down to 0.001 V from OCV (3.5 V) revealed that about 35 Li+ could possibly be inserted into Li2Co2(MoO4)3 during the first discharge (reduction) corresponding to a specific capacity amounting to 1,500 mAh g-1. This is roughly fourfold higher compared to that of frequently used graphite electrodes. However, about 24 Li+ could be extracted during the first charge. It is interesting to note that the same amount of Li+ could be inserted during the second Li+ insertion process (second cycle discharge) giving rise to a second discharge capacity of 1,070 mAh g-1. It was also observed that a major portion of lithium intake occurs below 1.0 V vs Li/Li+, which is typical of anodes being used in lithium-ion batteries. © 2007 Springer-Verlag.